Penerapan Aromaterapi Lavender Terhadap Nyeri Akut Pada Pasien DM Di Desa Tambang - M. Bayu Anggara; Nila Kusumawati; Riani Riani (Excellent Health Journal, 2025)
Diabetes mellitus, if uncontrolled, can cause various serious complications in the body, including damage to blood vessels, nerves, kidneys, eyes, and heart. These complications can be fatal and reduce the quality of life of sufferers. Treatment of DM is with pharmacological and non-pharmacological techniques. One of the non-pharmacological techniques for treating DM is lavender aromatherapy to reduce pain intensity and blood sugar levels in DM sufferers. The design of this study is a case study involving 1 respondent, namely Mrs. F. This study was conducted on August 19-21, 2024, starting from the assessment, data analysis, diagnosis, intervention, implementation, and evaluation stages. The results of the study showed that there was an effect of applying lavender aromatherapy on pain intensity and blood sugar levels in Mrs. F, the pain scale from 5 to 3 and blood sugar levels from 250 mg/dl to 180 mg/dl. It is hoped that Mrs. F will always apply lavender aromatherapy in controlling blood sugar levels so that they remain stable (normal conditions).